Ocean Dynamics and Methane Plume Activity in Tatar Strait, Far Eastern Federal District, Russia as Revealed by Seawater Chemistry, Hydroacoustics, and Noble Gas Isotopes - Snyder, Glen Tritch; Yatsuk, Andrey; Takahata, Naoto; Shakirov, Renat; Tomaru, Hitoshi; Tanaka, Kentaro; Obzhirov, Anatoly; Salomatin, Aleksandr; Aoki, Shinsuke; Khazanova, Elena; Maryina, Evgeniya; Sano, Yuji; et al. (Frontiers in Earth Science, 2022)
Located between Sakhalin Island and the Russian Far Eastern districts of Primorski Krai and Khabarovsk Krai, the Tatar Strait comprises the northernmost part of the Japan Sea. Research over the past several decades has shown that shown that the temperature and salinity in the shallow and subsurface water layers of the strait is sensitive to the balance between cold, less saline waters contributed by the Amur River to the north, and warm, saline waters of the Tsushima Current which migrates northward along the eastern margin of the Japan Sea. Our research presents major gas, noble gas isotopes, CTD, and stable isotopic data for water samples collected with Niskin bottles in Tatar Strait during the Spring of 2015 and 2019 onboard the Russian RV M.A. Akademik Lavrentyev. Of particular interest are gas plumes found along the eastern margin of the strait off the coast of Sakhalin Island. These plumes were detected using shipboard hydroacoustic instrumentation, and sampling for noble gases focused on these sites. The purpose of this research was twofold. The first was to determine the current distribution of water masses in the strait and to see if any discernible difference is present when comparing to dissolved gas measurements taken two decades previous. The second was to determine if the gas plume activity has an influence on circulation and methane accumulations in water masses along the margins of the strait. Even though methane gas is clearly observed through migrating through intermediate waters in these sites, we found that the deeper intermediate waters still retain tritiogenic 3He, similar to that observed throughout much of the Japan Sea. While our data is limited, the surface, subsurface and intermediate water layers do show distinct annual variation which is consistent with an instability in the interactions between subtropical Tsushima Current and the subpolar waters of the Primorye Current as a result in fluctuations in Amur River discharge.